Clinical results of basal meningiomas laser surgery - V. V. Stupak; A. V. Kalinovsky; S. V. Maiorov; S. G. Struts (Бюллетень сибирской медицины, 2008)
Methods of surgical treatment of patients with skull base meningiomas using high intensity infrared laser radiation (ND-YAG laser) at a wavelength of 1.06 micron were developed. The paper presents results of Nd-YAG laser application in skull base meningioma removal with assessment of its efficacy as compared with conventional surgical methods.